2008
DOI: 10.1002/mabi.200800053
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Genipin‐Crosslinked Chitosan/Silver Nanoparticles ‐ Structural Reinforcement and Antimicrobial Properties

Abstract: This study investigates the feasibility of a novel nanocomposite (GC/Ag) of a genipin-crosslinked chitosan (GC) film in which was embedded various amounts of Ag nanoparticles for wound-dressing applications. In situ UV-vis results revealed that adding chitosan solution did not affect the characteristics of Ag nanoparticles. The water uptake ratios and surface hydrophilicity of the GC/Ag nanocomposite were better and the degradation rates slightly lower than those of the pure GC film. The presence of Ag nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…This has improved the material properties dramatically especially on the mechanical level due to the extremely high surface to volume ratios 242,243 . Furthermore, inclusion of nanoscale into biopolymers also improved cell biocompatibility 244 , antibacterial and antiviral properties [245][246][247][248][249] .…”
Section: The Use Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has improved the material properties dramatically especially on the mechanical level due to the extremely high surface to volume ratios 242,243 . Furthermore, inclusion of nanoscale into biopolymers also improved cell biocompatibility 244 , antibacterial and antiviral properties [245][246][247][248][249] .…”
Section: The Use Of Nanoparticlesmentioning
confidence: 99%
“…It has been shown that combining chitosan or modified chitosan with Ag into composites resulted in films and hydrogel materials with enhanced cell antimicrobial activity, increased tensile strength, but decreased water vapour permeability 79,244,263 . The chitosan-Ag films yielded a significant reduction in the number of viable bacterial colonies compared to the control sample for both Gram-positive and Gram-negative bacteria 244 .…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Due to the hydrophilic nature of polysaccharides, firstly the nanoparticles are dispersed in water and then, the encapsulation can be performed by the homogeneous mixing of the nanoparticles hydrosol with an aqueous solution of the biopolymer. This route has been extensively used for the preparation of functional nanocomposites of chitosan (Liu & Huang, 2010;Matteini et al, 2010), alginate (Brulé et al, 2011;Marsich et al, 2011), dextran www.intechopen.com ) and gum arabic (Banerjee & Chen, 2007) amongst other polymers, containing dispersed inorganic phases, such as magnetic (e.g. iron oxides) and optical active (e.g.…”
Section: Bulk Nanocompositesmentioning
confidence: 99%
“…However studies from the last decade have revealed that silver nanoparticles have improved antibacterial properties than bulk silver and that even nanomolar concentrations of silver nanoparticles can be more effective than micromolar concentrations of silver ions (Kong & Jang, 2008), thus leading to an increased interest on materials comprising nano-silver. In this context, a number of polysaccharide based silver nanocomposites have been reported (Liu & Huang, 2010;Kemp et al, 2009a;Travan et al, 2009;Vimala et al, 2010). These materials exhibit antimicrobial activity and may be considered for applications in wound dressings and for water purification purposes.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…On the other hand, the host polymers can influence the growth and spatial arrangement of the nanoparticles during the in situ synthesis, which makes them convenient templates for the preparation of nanoparticles of different morphologies. Furthermore, by selecting the polymer with certain favorable properties such as biocompatibility [35], conductivity [36] or photoluminescence [37], it is possible to obtain the nanocomposite materials for various technological purposes.…”
Section: Metal-polysaccharide Nanocompositesmentioning
confidence: 99%